Virilization in a Girl with Adrenocortical Adenoma: A Case Report (Ibrahim Medical College Journal, 2013)
We present a case of Cushings syndrome and virilization in a 15 year old girl which was suspected to be due to an adrenal carcinoma. She presented with features of virilization in addition to those of hypercortisilism. Her high androgen levels especially dehydroepiandrosterone sulfate (DHEAS) were also in favor of an adrenal carcinoma. An unenhanced computerized tomography (CT) scan showed a mass (size: 5.3 cm) in the right adrenal gland with a soft tissue intensity of more than 10 HU which was suggestive of adrenal carcinoma. But, histopathology of the resected mass revealed a benign adrenocortical adenoma. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14736 Ibrahim Med. Coll. J. 2012; 6(2): 70-72